Brand Promotion : A Case Study of Air Conditioners - Selvarasu, A.; Kumar, S. Senthil (Indian Journal of Marketing, 2004)
Brand is essentially a seller's promise to consistently deliver a specific set of features, benefits and services to the buyers. The best brands convey a warranty of quality. But a brand is even a more complex symbol. A brand is a name, term, sign, symbol or design, or a combination of them, intended to identify the goods or services of one sellers or group of sellers and to differentiate them from those of competitors. In essence, a brand identifies the seller or maker. It can be a name, trademark, logo or other symbol under trademark law; the seller is granted exclusive rights to the use of the brand name in perpetuity. Chitra Balasubramanium (2003) has reported that market potential for AC is Rs.3000 Crores in the Industry market according to the findings given by Mckinsey & Co. The report has brought out three fold bounds and barriers in the industry in terms of costs such as lifecycle cost of ownership of air conditioners, running costs of electricity and annual maintenance costs. By keeping pace with solving these problems, the projected growth rate is 55 percent in household air conditioners and about 20 percent in commercial air conditioning and refrigeration. Further, it is informed that the export market and service business has the potential to grow to Rs. 1200 Crores and Rs.500 Crores respectively.